Sistema de automação e controle para cultivo protegido utilizando web services e integração de serviços de cloud computing da azure - Testa, Gabriel Henrique (2023)
In this study, we propose the implementation of an infrastructure capable of accommodating environmental climate measurement sensors within a greenhouse for plant cultivation, providing the possibility of remote monitoring and control through internet-connected devices, such as smartphones and computers. The aim is to acquire, record, analyze, and send data from all measured variables with low latency to a cloud infrastructure, where the data can be accessed by APIs or mobile applications, as well as providing an API for sending commands and automatic climate parameterization programming. To validate the model, performance tests were conducted to ensure the full functionality of the architecture. This involved transferring data from its inception in sensors, passing through the entire VPN pipeline, cloud gateways, processing queues, and data processing servers to the database. Data was also transferred in the opposite direction, enabling it to send commands to local devices from the internet. Due to the highly competitive market, producers seek the use of available technologies to increase productivity and ensure their presence in the market. Currently, the integration of cloud computing technologies has revolutionized the way we understand applications that previously had no connectivity. This work aims to integrate three areas of knowledge: agriculture, electronics, and information technology, applying emerging concepts such as the Internet of Things, Big Data, and Business Intelligence, in addition to current computing techniques. Besides providing the unitary infrastructure, this study also proposes to construct a structure capable of acquiring a large amount of data from various clients, applying information security concepts to ensure that the data is timely and secure. Additionally, the project aims to offer numerous possibilities for future improvements and deliver a highly professional product.